Peningkatan Pengetahuan Dosen Dalam Publikasi Penelitian di Jurnal Internasional Melalui Kegiatan Workshop Scientific Writing - Dian Agnesa Sembiring; Aliya Azkia Zahra; Sekar Ayu Runggandini; Iha Nursolihah; Astri Nurdiana; Al Mukhlas Fikri (Intitut Agama Islam Nasional Laa Roiba Bogor, 2023)
Based on a brief survey conducted by the author to 40 lecturers at FIKES UNSIKA (Faculty of Health Sciences, Universitas Singaperbangsa Karawang) on September 5, 2022, it was found that the number of lecturers who had never written scientific publications indexed by Scopus and WoS was 17 lecturers (43.6%). And in an effort to reduce these problems, it is necessary to socialize and educate about research publications in international journals in the form of workshop activities. Evaluation of participants in scientific writing workshop activities for internationally reputable journals was carried out using pre-test and post-test methods. Based on the results of the pre-test and post-test, it is known that the participants' knowledge has increased overall. And overall the evaluation of the workshop participants' assessment related to the evaluation of organizing activities is good and very good. The participants' suggestions for organizing workshop activities in the future so that they can be scheduled regularly, continuously, and continuously and it is hoped that in the future they will hold a journal article clinic with one on one coaching until submitting the manuscript. Keywords: Workshop, Publication, International Journal, Lecturer, Knowledge